The Double Bond of Interpretation: Conservation and Innovation of Tradition (Itinera, 2015)
The crisis of hermeneutical philosophy is an important opportunity for a reflection on the adaptive forms of rationality. The present essay aims at clarifying two issues of adaptiveness in a hermeneutical perspective: the overturning of the traditional relationships between theoria and praxis; and the place of the rule-violation in this pragmatical view of rationality. Metaphor is the most significant example of this adaptiveness.